Amlodipine, an L-type Ca2+ channel inhibitor, regulates release of extracellular vesicles from tumor cells - Mondal, Sujan K; Hong, Chang-Sook; Han, Jie; Diergaarde, Brenda; Zandberg, Dan P; Whiteside, Theresa L (Carcinogenesis (New York), 2025)
Tumor cells produce/release tumor-derived exosomes (TEX) which promote tumor growth, drive immune suppression, and interfere with immune therapies. Amlodipine, a calcium flux inhibitor, may block TEX release by tumor cells. Amlodipine’s potential as a drug blocking TEX release was evaluated. We measured tumor growth, TEX numbers, phenotype, and molecular content in murine SCCVII and human cancer cell lines. Cell lysates and TEX were tested for expression of autophagy-related proteins by western blots (WBs). Tumor growth in mice, histopathology, T-cell infiltrations, and TEX production by SCCVII treated with amlodipine were measured. Numbers and protein content of TEX eluted from tumor explants were studied by flow cytometry and WBs. Amlodipine used in vitro at 0.5–5 µM was nontoxic, did not impair tumor cell viability, reduced cell proliferation, and decreased TEX production. It reduced PD-L1 and Rab11 content of TEX, altered tumor cell size/shape, induced vesicle accumulations in the cytosol, and upregulated expression levels of autophagy-related proteins, ATG7, Beclin-1, and LC3. In vivo, daily treatment of established SCCVII with amlodipine (10 mg/kg) inhibited tumor growth (P < 0.001), increased CD8+ T-cell infiltration into tumor, decreased TEX production, and altered PD-L1, Rab11, and FasL content of TEX. Amlodipine delivered in vitro to tumor cells or in vivo to tumor-bearing mice interferes with tumor growth and TEX production, induces tumor autophagy, reduces circulating TEX numbers, and alters the TEX immunosuppressive signature. Amlodipine emerges as a potentially promising drug for removing immunosuppressive TEX in cancer subjects who are candidates for immune therapies.